2011
DOI: 10.1103/physrevb.84.104446
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic phase diagram of CeAu2Ge2: High magnetic anisotropy due to crystal electric field

Abstract: CeAu 2 Ge 2 single crystals (with tetragonal ThCr 2 Si 2 structure) have been grown in Au-Ge flux (AGF) as well as in Sn flux (SF). X-ray powder diffraction and EDX measurements indicate that in the latter case, Sn atoms from the flux are incorporated in the samples, leading to a decrease of the lattice constants by ≈0.3% compared to AGF samples. For both types of samples, a strong anisotropy of the magnetization M for the magnetic field B parallel and perpendicular to the c direction is observed with M || /M … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Their magnetism is commonly determined by a large magneto-crystalline anisotropy. This leads to the presence of distinct field-induced metamagnetic transitions [8][9][10][11][12][13][14][15] . Depending on the strength of the magnetic anisotropy, the nature of the metamagnetic transition(s) may differ.…”
Section: Introductionmentioning
confidence: 99%
“…Their magnetism is commonly determined by a large magneto-crystalline anisotropy. This leads to the presence of distinct field-induced metamagnetic transitions [8][9][10][11][12][13][14][15] . Depending on the strength of the magnetic anisotropy, the nature of the metamagnetic transition(s) may differ.…”
Section: Introductionmentioning
confidence: 99%
“…If the hybridization between f electrons and conduction electrons is very weak, the ground states of these systems are dictated by RKKY exchange interaction and crystal electric field (CEF) effects, resulting in long-range magnetic order. [14][15][16] In the case of the Ce local moment metals without the Kondo effect, the ordering temperatures range from T C = 115 K 17,18 in ferromagnetic CeRh 3 B 2 , to T N = 2.75 K 19 in antiferromagnetic (AFM) CeSbTe, while much lower temperatures can be expected for the Yb analogues 20 . Lower ordering temperatures in both Ce 3+ and Yb 3+ compounds could occur from any combination of effects including Kondo, competition between different exchange interactions, strong CEF anisotropy, or large distances between rare-earth ions (d R−R ) that minimize the RKKY exchange coupling J RKKY .…”
mentioning
confidence: 99%
“…The magnetic susceptibility of CeAu 2 Ge 2 exhibits strong anisotropy with an easy [001] direction perpendicular to the tetragonal plane. 16,17 Previous measurements on a powder of CeAu 2 Ge 2 showed that the correlated Ce-ions develop a long range antiferromagnetic order below T N 16 K. 13 In this article, we report elastic neutron scattering measurements on a high quality single crystal sample of CeAu 2 Ge 2 . The crystals were synthesized by high temperature solution growth method using Bi flux and the quality was verified using X-ray measurements.…”
mentioning
confidence: 99%
“…13,16,17 However, as the sample is cooled below 10 K new magentic peaks start appearing with different temperature dependencies. As shown in the series of plots in Fig.…”
mentioning
confidence: 99%